Effects of carcass weight, sex and breed composition on meat cuts and carcass trait in finishing pigs - Lei XIE; Jiang-tao QIN; Lin RAO; Deng-shuai CUI; Xi TANG; Shi-jun XIAO; Zhi-yan ZHANG; Lu-sheng HUANG (Journal of Integrative Agriculture)
Pork cutting is a very important processing in promoting economic appreciation across the swine business chain. The goal of this research is to determine the proportion and weight of meat cuts, as well as to analyze the effects of carcass weight, sex and breed composition on meat cuts. Simultaneously, we investigate the correlation between meat cuts, carcass traits and meat quality traits. To assess 17 meat cut traits, 12 carcass traits and 6 meat quality traits, we sample 2 012 pigs from four breeds, including Landrace (LD), Yorkshire (YK), Landrace Yorkshire (LY), and Duroc Landrace Yorkshire (DLY). The results showed that carcass weight, sex and breed composition have significant effects on the weight and proportion of most meat cuts. The proportion of cuts for muscle and bone decrease as carcass weight grows, whereas the proportion of cuts for fat increases. Moreover, the thickness of four-point backfat was significantly increasing (P<0.001) with increase of carcass weights, indicating that large amount of intaking energy in the late finishing stage was used for fat deposition. Besides, the proportion of Shoulder cut (SC) and Back fat (BF) in barrows was significantly higher (P<0.001) than that in sows, whereas the Leg cut (LC) showed the opposite trend. The Loin (LO) proportion and Loin muscle area (LMA) of barrows were significantly lower (P<0.001), but the proportion of fat areas in the image (PFAI) and visual marbling score (VMS) were significantly higher (P<0.001) than those of sows, respectively. In terms of breeds, LD had the longest straight carcass length, significantly longer (P<0.001) than the other three breeds, which partially explains why LD had the largest proportion of the Middle cut (MC). Moreover, the proportion of SC in DLY was the highest. Last but not least, the correlations between the proportions of most meat cuts, and also between meat cuts and meat quality or carcass traits were low or not significant (P>0.05). The effects of carcass weight, sex and breed composition on the meat cuts, meat quality and carcass traits are breed and growth stage dependent. It also reflects the asynchrony of the growth curve between different sexes. Our results laid an important foundation for breeding pig carcass cuts and composition.